PENGARUH PENGGUNAAN MACROMEDIA FLASH 8.0 TERHADAP HASIL BELAJAR DASAR LISTRIK DAN ELEKTRONIKA - Muthie Anggyt Pratiwi; Ilmiyati Rahmy Jasril (Universitas Negeri Padang, 2019)
The purpose of this study was to determine how much influence the use of interactive learning media based on Macromedia Flash 8.0 on learning outcomes Basic Electricity and Electronics (DLE) Audio Video Engineering class X in SMK Negeri 5 Padang. Researchers use the Quasi Eksperiment Design. The subject of this study consisted of 2 classes, namely class X TAV1 as an experimental class and class X TAV2 as a control class. The sampling technique in this study was conducted by purposive sampling or based on certain considerations. How to retrieve data use posttest at the end of learning after each class is given treatment. This can be seen from the learning outcomes of experimental class students who obtained an average of 81,90 higher while the value of the control class that got an average 70,20. Based on the hypothesis test, the value of tcount 5,879 > ttable 1,677, it can be said that there is a significant effect on the implementation of learning using macromedia flash 8.0. Keywords: Interactive learning media, macromedia flash 8.0, learning outcomes.